Nutcracker syndrome - a mini review on current knowledge - Kramek, Jakub Tomasz; Krasiński, Zbigniew; Stępak, Hubert (Journal of Medical Science, 2021)
Nutcracker syndrome (NCS) seems to be an under-diagnosed condition defined as external compression of the left renal vein and consequent blood outflow impairment. The majority of cases involve the left renal vein entrapment between abdominal aorta and the superior mesenteric artery. The exact epidemiology is unknown due to lack of consensus on diagnostic criteria and often asymptomatic courses. NCS may occur at any age with peak presentation in the second and third decade of life. There is a slight prevalence in females. The most frequent presentations include micro and macroscopic hematuria, orthostatic proteinuria, orthostatic hypotension, flank pain. Patients may develop pelvic congestion syndrome comprising dyspareunia, dysmenorrhea, abdominal pain, pelvic, gluteal, vulvar varicose veins and varicocele in men. Clinical suspicion of NCS based on signs and symptoms, requires imaging confirmation utilising modalities such as doppler ultrasonography, computed tomography and magnetic resonance angiography, intravascular ultrasound and phlebography. Treatment options of NCS range from conservative surveillance to nephrectomy, thus appropriate approach should be based on clinical manifestation and severity of symptoms. Patients presenting with mild to moderate haematuria, and acceptable symptoms should be treated conservatively. In cases of severe symptoms or when conservative management fails, invasive treatment should be considered. Recommended open surgical procedures include left renal vein distal transposition and renal autotransplantation. Endovascular stenting approach seems to be an encouraging solution. Further long term follow-up is required to create objective treatment guidelines.